PERENCANAAN ANGGARAN, POLITIK ANGGARAN, DAN PELAKSANAAN PENGADAAN BARANG/JASA TERHADAP PENYERAPAN ANGGARAN (Studi Pada OPD Kabupaten Rokan Hilir) - Murhanita, Murhanita; Edfan, Darlis; Yuneita, Anisma (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2020)
This research aims to examine and analyze the effect of budget planning, budget politics, and implementation of goods/services procurement on budget obsorption. This study used the primary data. The population in this study were the regional apparatus organization (OPD) in Rokan Hilir’s regional goverment. This study used purposive sampling method. The data that could be analyzed were 71 data. Data was collected through a questionnaire. Data were analyzed using multiple linear regression analysis with the SPSS program version 23. The result of this study showe that budget planning and implementation of goods/services procurement influence of budget absorption. While budget politics has not effect on budget absorption.Keyword: Budget Absorption, Budget Planning, Budget Politics, and Implementation of Goods/Services Procurement.